1999
DOI: 10.1021/ma981917+
|View full text |Cite
|
Sign up to set email alerts
|

Interaction between Radicals Derived from Two Di-t-Alkyl Peroxides with Some Monomers and Polymers

Abstract: The thermolysis of di-tert-butyl and di-t-amyl peroxides in n-decane and with poly(methyl methacrylate) and poly(ethylene glycol) in chlorobenzene has been studied in the presence of tri-tert-butylnitrosobenzene as a spin trap. The major reaction pathways of the resulting t-alkoxyl radicals were β-scission and hydrogen atom abstraction. Thermolysis of the same peroxides in the presence of methyl methacrylate and methyl acrylate led to the trapping of growing polymer chains alongside unreacted alkyl radicals (a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
30
1

Year Published

2000
2000
2014
2014

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 23 publications
(32 citation statements)
references
References 18 publications
1
30
1
Order By: Relevance
“…Besides the effect of P M / P sat , temperatures of the filament (T f ) can also affect the deposition rate in the synthesis of PDVB-MA. Previous publication indicates the degree of decomposition of TBPO increases as T f increases when T f < 270 °C, and higher T f results methyl radicals [40], which is more reactive than the tert-butoxy radicals and therefore accelerate the freeradical polymerization. [41] 3.2 Conformality, uniformity, and surface roughness…”
Section: Characterization Of Pdvb-mamentioning
confidence: 98%
“…Besides the effect of P M / P sat , temperatures of the filament (T f ) can also affect the deposition rate in the synthesis of PDVB-MA. Previous publication indicates the degree of decomposition of TBPO increases as T f increases when T f < 270 °C, and higher T f results methyl radicals [40], which is more reactive than the tert-butoxy radicals and therefore accelerate the freeradical polymerization. [41] 3.2 Conformality, uniformity, and surface roughness…”
Section: Characterization Of Pdvb-mamentioning
confidence: 98%
“…Abstraction is not expected to occur significantly at methyl carbons because of a larger bond dissociation energy in comparison with the other two available types of hydrogens. 21 However, in a recent article by Mekarbane and Tabner, 29 hydrogen abstraction from the methyl groups in n-decane by radicals derived from di-t-butyl peroxide was observed in experiments with 2,4,6-tri-tert-butylnitrosobenzene (TTBB) as a spin trap. The results demonstrated that ϳ64% of the resulting spintrap products were derived from secondary carbon-centered radicals.…”
Section: -Dodecenementioning
confidence: 99%
“…6 -10 On the other hand, the much fasterˇ-scission of tert-amyloxyl radicals compared with tert-butoxyl radicals 10 -12 leaves the ethyl radical, a much poorer hydrogen atom abstractor, as the major initiating species. 6,9,10 Variation of R 0 (in 1) also provides a convenient means of altering activity as the thermal stability of the peroxide varies with the steric nature of both R and R 0 , decreasing as the steric bulk of these groups increases. 1 In addition to theˇ-scission of tert-alkoxyl radicals the decarboxylation of acyloxyl radicals [Scheme 1, Eqn (2)] is a well known route to alkyl radicals.…”
Section: Introductionmentioning
confidence: 99%
“…We selected the symmetric bis(3,5,5-trimethylhexanoyl) peroxide (2) in anticipation that thermolysis should initially produce two identical acyloxyl moieties (but no alkoxyl moiety) and the closely related tert-butylperoxy-3,3,5-trimethylhexanoate (3) which (during thermolysis) would be expected to produce the same acyloxyl moiety as 2 and the tertbutoxyl radical whose reactions during the thermolysis of several peroxides have been reported in detail. 6,12 The remaining two peroxides selected were tert-amylperoxy-2-ethylhexanoate (4) and the bifunctional peroxide 2,5-dimethyl-2,5-bis(2-ethylhexanoylperoxy)hexane (5), both of which might be expected to produce the same acyloxyl moiety as one another.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation